Determinants influencing attitude, intention and engagement toward circular economy: Empirical evidence in food industry - Truong, Dinh Chien; Nguyen, Khoa Huu Dang; Nguyen, Dinh Toan; Truong, Linh (Edelweiss Applied Science and Technology, 2024)
The study was conducted to investigate determinants influencing attitude, intention, and engagement toward circular economy adoption in the context of the food industry in Vietnam. Structural equation modelling (SEM) was employed to test the hypotheses with the survey data of 513 respondents in the two biggest cities of Hanoi, and Ho Chi Minh City. The results reveal that environmental awareness, motivation, and benefits of adopting circular economy, regulations, laws, and individual reputation in the community, trust and belief have significant positive impacts on attitude and intention. In addition, attitude has a significant positive effect on engagement intention toward circular economy. Intention also has a significant positive effect on engagement behavior toward circular economy. The study’s empirical analysis carries implications for managers when implementing the circular economy model. Policy makers and managers can use the research outcomes in their decision making toward social programs, in which more guidance is provided to the public audience and the details of each process are introduced with tools and equipment that are accessible to individuals.